2021
DOI: 10.3390/nu13072256
|View full text |Cite
|
Sign up to set email alerts
|

Association between Mobile Phone Addiction Index and Sugar-Sweetened Food Intake in Medical College Students Stratified by Sex from Shanghai, China

Abstract: This study’s objective was to depict sugar-sweetened food (SSF) consumption in medical college students stratified by sex from Shanghai, China, and to explore the association between the Mobile Phone Addiction Index (MPAI) and SSF intake. The data were obtained from 1121 medical college students from the Fudan University, Shanghai, China, who took an online questionnaire investigation in December 2020. Data included demographics, the MPAI, the Nutrition Literacy Assessment Questionnaire (NLAQ), total and food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…In contrast, age, grade, faculty-student relationship, insomnia, cigarette use, BMI, and life satisfaction were significantly associated with mental health. These findings echoed prior observations on the determinants of mental health for college students (Lopez-Fernandez et al, 2014;Fergusson et al, 2015;De-Sola Gutiérrez et al, 2016;Bieda et al, 2018;Cha, 2018;Zhen et al, 2019;Nie and Ma, 2020;China Internet Network Information Center, 2021;Jiang et al, 2021;Liu et al, 2021). Notedly, in this study, having higher life satisfaction was associated with lower odds of suffering from psychological problems for college students, which indicated life satisfaction's role in reducing the psychological problems.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In contrast, age, grade, faculty-student relationship, insomnia, cigarette use, BMI, and life satisfaction were significantly associated with mental health. These findings echoed prior observations on the determinants of mental health for college students (Lopez-Fernandez et al, 2014;Fergusson et al, 2015;De-Sola Gutiérrez et al, 2016;Bieda et al, 2018;Cha, 2018;Zhen et al, 2019;Nie and Ma, 2020;China Internet Network Information Center, 2021;Jiang et al, 2021;Liu et al, 2021). Notedly, in this study, having higher life satisfaction was associated with lower odds of suffering from psychological problems for college students, which indicated life satisfaction's role in reducing the psychological problems.…”
Section: Discussionsupporting
confidence: 87%
“…One study showed more frequent cell phone overuse among college students when compared with the pre-epidemic period (Kim, 2018 ). Additionally, it was also reported that frequent use of the internet on cell phones among college students would cause poor sleep quality, irregular eating patterns, and even anxiety and depression (Liu et al, 2021 ). Within the Chinese context, according to a report from the China Internet Network Information Center (CINIC), up to December 2020, there were 1.614 billion mobile phone users in China, among whom students accounted for 21%, with college students aged 18–22 being the largest- and fastest-growing group (China Internet Network Information Center, 2021 ; Conrad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting finding of our study is that the MAPI score was lower than in several previous studies. For example, Liu et al found that the MPAI score in male medical college students in Shanghai was 44.94 ± 12.08, female 45.25 ± 11.87 ( 41 ). A study of high school students in Sichuan and Chongqing showed a little higher MPAI score with a mean of 41.65 than our study ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sampling method was previously described [ 32 ], and random cluster sampling was applied. Four colleges and departments were randomly selected from the medical school of Fudan University, Shanghai, China, including the School of Public Health, the School of Basic Medicine, the Institute of Brain Science, and the Institute of Biomedicine.…”
Section: Methodsmentioning
confidence: 99%
“…In December 2020, we conducted an online questionnaire survey for our target population. The survey method was previously described [ 32 ]. The online questionnaire survey was conducted via “Wenjuanxing” ( , accessed on 12 December 2020), a platform providing functions equivalent to Amazon Mechanical Turk.…”
Section: Methodsmentioning
confidence: 99%